The integrated evaluation as a driving tool for cultural-heritage enhancement strategies. - Della Spina, Lucia (Springer, 2018)
The paper shows the setting up of an integrated evaluation process to identify a sustainable enhancement strategy for a particularly significant territory in southern Italy that expresses the concept of Historic Urban Landscape (HUL) proposed by the UNESCO. The evaluation process is flexible to adapt to the specificity of complex contexts, to enable interaction with heterogeneous knowledge and to capture local values associated with the particular dimensions of a multi-scalar system. The evaluation is defined as a multidimensional, dynamic, incremental and cyclical learning process, which combines evaluation techniques integrated with public-participation techniques in order to delineate shared and transparent intervention strategies. Through a shared observation process of the context have been identified the values and resources, the key stakeholder categories and their preferences. Selecting context-aware actions enables us to reduce the conflicts by transforming them into synergies, recognizing as essential the components of a constantly evolving, multidimensional and complex landscape in which various systems of values and relationships interact. A 'tailor-made' multi-methodological approach that is enables the combination of the approaches of the Soft-System Methodology, Multi-Criteria Analysis and Multi-Group Analysis with the purpose of identifying the components of the perceived scenario and developing a strategic map able to put in network a system of micro actions, material and immaterial, sensitive to context specificities.
Keywords: Entscheidungstheorie; Spieltheorie; Kulturerbe; Kulturgut; Partizipation; Regionalplanung